The effect of digital supply chain on organizational performance: An empirical study in Malaysia manufacturing industry - Lee, Khai Loon; Nurul Ain Najiha, Azmi; Hanaysha, Jalal Rajeh; Alzoubi, Haitham M.; Alshurideh, Muhammad Turki (Growing Science Ltd., 2022)
Nowadays, global technologies, especially digital things, have become an important tool for businesses to maintain feasible partnerships and build a great value connection with other companies. New digital technologies that are emerging every day are on their way to affect nearly all business processes and activities. This study investigates the effect of the digital supply chain on the supply chain and organization performance in the Malaysia manufacturing industry. This paper also further assesses the mediating effect of supply chain performance in the relationship between the digital supply chain and the organizational performance in the Malaysia manufacturing industry. The objectives are achieved via quantitative research design. The researchers emailed the online survey questionnaire to 1160 manufacturing companies listed in the Federation of Malaysian Manufacturers (FMM) directory via stratified sampling technique and received 63 responses. 7 incomplete responses have been deleted and 56 usable responses representing 5.43% of the response rate used for data analysis. The data was analyzed by using the Partial Least Square Structural Equation Modeling (PLS-SEM). Three hypotheses are not supported and seven hypotheses are supported, which includes all the hypotheses of moderating effect. The manufacturing companies in Malaysia can consider adopting the DSC in the business process to remain reliable in the competitive market by providing good supply chain performance and best organizational performance as a whole. The implication of the study is given to academics and practitioners, specifically manufacturing companies. The limitations and the recommendation for future study have been highlighted.